(untitled) (diségno, 2024)
Hosted in the evocative Rotonda Talucchi of the Accademia Albertina di Belle Arti di Torino, from September 24th to October 29th, 2024, the exhibition Lizori. Segni e Dialoghi offers an experience of artistic and cultural reflection dedicated to the regeneration of Italy’s historic burgs. Focusing on Lizori, a medieval Umbrian burg located in the municipality of Campello sul Clitunno in the province of Perugia, the exhibition explores the possibilities of restoring and enhancing historical and cultural roots, reflecting on the deep bond that links architecture to the landscape and collective memory. The burg of Lizori, with cobbled streets, stone houses, and perimeter walls that preserve its ancient defensive character, becomes a symbol of a heritage that is capable of speaking to both the present and the future with a vibrant, layered cultural identity. [read more]